Empowerment and Training of D4 Applied English of FBS UNM Students in Ornamental Plant Business Management: Pemberdayaan dan Pelatihan Mahasiswa D4 Bahasa Inggris Terapan FBS UNM dalam Pengelolaan Usaha Tanaman Hias - Jefri, Riny; Wahid, Abdul; Hajar, Andi; Amin, Fatimah Hidayahni; Sunusi, Seny Luhriyani (Mattawang: Jurnal Pengabdian Masyarakat, 2024)
The occurrence of Covid-19 resulted in a decrease in people's income levels which was also experienced by several student families, especially in the UNM Applied English study program. These problematic conditions became the reason for the service team to plan community service activities for students of the Bahasa Inggri Terapan D4 FBS UNM. This service activity is carried out in the form of a seminar as an introduction to ornamental plant entrepreneurship, ornamental plant business management and how to do online marketing. This seminar is an introductory stage and a discussion session to share experiences in managing an ornamental plant business, so that students can participate and be successful with their ornamental plant business in the future. It is hoped that the ornamental plant business can help their family's economy so that they can focus more on continuing their studies in the future. Abstrak Terjadinya Covid-19 mengakibatkan penurunan tingkat penghasilan masyarakat juga dialami oleh beberapa keluarga mahasiswa khususnya di prodi Bahasa Inggris terapan UNM. Kondisi permasalahan tersebut menjadi alasan bagi tim pengabdi untuk melakukan rencana kegiatan pengabdian kepada masyarakat bagi mahasiwa Prodi Bahasa Inggris Terapan D4 FBS UNM. Kegiatan pengabdian ini dilaksanankan dalam bentuk seminar sebagai pengenalan kewirausahan tanaman hias, managemen pengelolaan usaha tanaman hias dan bagaimana melakukan pemasaran secara online. Seminar ini merupakan tahap pengenal dan sesi diskusi share pengalaman mengelola usaha tanaman hias, agar para mahasiswa dapat mengikuti dan sukses dengan usaha tanaman hias mereka dikemudian hari. Usaha tanaman hias diharapkan dapat membantu perekonomian keluarga mereka sehingga mereka dapat lebih fokus melanjutkan tugas studi mereka dimasa depan.